Federal State Fiscal Equalisation 2020: New Scheme — Old Problems - Wolfgang Scherf (Wirtschaftsdienst)
Abstract The new federal state fiscal equalisation will be implemented for the first time in 2020. Its functioning and effects are presented and illustrated in detail. Compared to the old system, there are large formal differences but only minor real differences. The reform has not eliminated existing deficits, but rather exacerbated them. The author proposes a model for a further reform of the federal state fiscal equalisation to improve the incentive effects.